PENENTUAN SENSITIVITAS YANG BERPENGARUH TERHADAP PRODUKSI RESERVOIR MULTILAYER SECARA COMMINGLE - Engeline Malrin Kuncoro; Risna Risna (PETROGAS: Journal of Energy and Technology, 2022)
Multilayer reservoirs are not uncommon in oil and gas fields. In optimizing production in multilayer reservoirs, commingle production is an option. When producing a multilayer reservoir, it is necessary to select a reservoir with suitable characteristics. More and more research in producing multilayer reservoirs by commingle is being carried out. Forchheimer conducted research on the effect of turbulence that occurs, especially in gas wells. This turbulence effect causes pressure disturbances from the reservoir into the well. When the reservoir is produced in commingle, how does gas turbulence affect the production. This research is devoted to the production of commingle wells that penetrate three layers of a multilayer dry gas reservoir by considering the turbulence that occurs. Then it is determined the possible sensitivity that has an effect using literature studies in the multilayer field and gas well field based on the cumulative changes in production that occur in each sensitivity.